Statistical Assessment of the Effectiveness of Transformation Change (by Case of Singapore) - ZhuravlyovО. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
In studies of economic transformations and their statistical assessment, the causality of processes specific to economic relations and development of institutions is overlooked. The article is devoted to the important topic of statistical assessment of the transformations effectiveness. The case of Singapore is taken because it is an Asian country demonstrating the essential role of the institutional environment in the national economy transformations. The regression analysis of the impact of institutional factors on economic growth in Singapore is made using 17 indicators: civil freedoms, corruption, economic freedom, economic globalization, spending on education, use of energy, share of women at labor market, fiscal freedom, price for fuel, PPP, effectiveness of public administration, level of consumption, Human Development Index, Internet users, life expectancy, unemployment, openness of trade. Economic interpretation of the statistical assessment of economic transformations in Singapore is as follows: quality of the institutional environment (control of corruption, economic freedom, supremacy of law etc.) has critical importance for economic development in Singapore; the increasing spending on education has positive effects for economic growth in Singapore; economic growth in Singapore has high positive correlation with energy consumption.